Heterotopic Nodules in the Placenta, an Immunohistochemical Re-evaluation of the Diagnosis of Adrenocortical Heterotopia. (January 2021) - Heerema-McKenney, Amy; Rabinowitz, Laura; Bendon, Robert; Bruehl, Frido; Blank, Alexander; Pinar, Halit
Background: Rare nodules of heterotopic adrenocortical and hepatic tissue are reported in the placenta. A mechanism for adrenocortical tissue in the placenta has been perplexing, while hepatic tissue is generally considered related to yolk sac primordia. The clear cell morphology of these nodules is similar to the adrenal cortex of the adult; however, the fetal adrenal gland does not usually display clear cells. Methods: We stained 9 placental nodules, histologically identical to "adrenocortical" heterotopia of the placenta, to determine whether adrenocortical differentiation could be confirmed. These cases include 3 archival cases initially diagnosed as "adrenocortical" heterotopia. Results: Immunohistochemical staining with steroid factor-1 (SF-1), HepPar-1, and Arginase-1 showed that these nodules of clear cells are actually hepatic (SF-1 negative, HepPar-1, and Arginase-1 positive). PAS staining suggests that glycogen accumulation is responsible for the clear cytoplasm. In contrast, a nodule of adrenocortical heterotopia near the testis and the adrenal gland from a 38-week-old neonatal autopsy case confirm SF-1 reactivity as expected. Conclusion: We propose that adrenocortical heterotopia in the placenta is a misnomer, and that these subchorionic nodules of clear cells demonstrate hepatic differentiation.